2015
DOI: 10.1039/c5ee01985k
|View full text |Cite
|
Sign up to set email alerts
|

A high performance sulfur-doped disordered carbon anode for sodium ion batteries

Abstract: Sulfur-doped disordered carbon exhibits high capacity and excellent cyclability as an anode for sodium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
315
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(336 citation statements)
references
References 44 publications
(67 reference statements)
18
315
0
3
Order By: Relevance
“…In SC-BDSA, the peak at 212 cm −1 belongs to the S-S chain-structure, while the stretching vibrations of C-S backbone is located at ≈355 cm −1 . [22,42] All of the S 2p XPS spectra can be deconvoluted into four peaks, which correspond to SS/CS bonds at around 164/165 eV, and sulfate species at about 168/169 eV, respectively. Figure 2c displays the X-ray photoelectron spectroscopic (XPS) survey spectra of the SC-BDSA, C-BDSA, and C-BSA, which show the pronounced XPS O 1s, C 1s, S 2p, and S 2s peaks at about 534, 285, 228, and 165 eV.…”
Section: Preparation and Physical-chemistry Features Of Sulfurized-camentioning
confidence: 99%
“…In SC-BDSA, the peak at 212 cm −1 belongs to the S-S chain-structure, while the stretching vibrations of C-S backbone is located at ≈355 cm −1 . [22,42] All of the S 2p XPS spectra can be deconvoluted into four peaks, which correspond to SS/CS bonds at around 164/165 eV, and sulfate species at about 168/169 eV, respectively. Figure 2c displays the X-ray photoelectron spectroscopic (XPS) survey spectra of the SC-BDSA, C-BDSA, and C-BSA, which show the pronounced XPS O 1s, C 1s, S 2p, and S 2s peaks at about 534, 285, 228, and 165 eV.…”
Section: Preparation and Physical-chemistry Features Of Sulfurized-camentioning
confidence: 99%
“…Unfortunately, the radius of Na þ (0.102 nm) is larger than that of Li þ (0.076 nm), which makes it difficult to find an appropriate host material with sufficiently interstitial space to accommodate Na þ [7]. Graphite, the typical LIBs anode with highly ordered layer structure, has been studied as the SIBs anode, but the specific capacity is low as it cannot store sufficient Na þ between its layers [8,9]. Non-graphitic carbonaceous materials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[ 138,269, The storage of Na in carbon materials such as hard carbon, amorphous carbon, defected graphene, and functionalized graphite has been observed to be thermodynamically feasible. [ 325,326,274,276 ] In the early works by Doeff et al, they demonstrated that the extent of Na intercalation in carbon materials varies depending on the carbon structure; NaC 70 , NaC 30 , and NaC 15 were formed for graphite, petroleum coke, and Shawinigan black, respectively.…”
Section: Non-graphitic Carbonmentioning
confidence: 99%
“…Later work by Chen et al revealed that the electrode operation involves a single-phase reaction with a negligible volume change (≈1.2%), resulting in a high rate and cycle performances. [ 138 ] Although various phosphate compounds have been introduced as new low-cost electrode materials for NIBs, they exhibit generally low energy densities below 400 Wh kg −1 and limited cycle stabilities.…”
Section: Phosphatesmentioning
confidence: 99%